Pengaruh Implementasi dari Sistem Informasi Pemerintah Daerah (SIPD) tentang Transparansi Keuangan Daerah pada Pemerintah Daerah - Atik Andhayani; Nurafni Eltivia (JUDICIOUS, 2022)
The level of quality of regional financial planning is highly dependent on the availability of accurate and complete data and information. Changes in realizing the quality of regional financial planning and transparency have been made by the government. The Local Government Information System (SIPD) is the government's effort in the process of supervision and transparency to the public. The purpose of this study was to examine the effect of SIPD implementation on regional financial transparency in the Batu City government. The population of this study is the Regional Apparatus Organization (OPD) in the form of an Agency / Office / Office. Based on the results of purposive sampling, the number of samples obtained was 20 OPDs. The data used is primary data. The analysis technique uses the PLS program. The results of this study indicate that SIPD has a very significant effect on regional financial transparency in the Batu City government. The better the quality of SIPD, showing good regional financial transparency to the public.